1986
DOI: 10.1111/j.1476-5381.1986.tb11139.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic actions of L‐DOPA on the release of endogenous noradrenaline and dopamine from rat hypothalamic slices

Abstract: Effects of L‐DOPA on the release of endogenous noradrenaline and dopamine from rat hypothalamic slices evoked by electrical field stimulation at 5 Hz were investigated in the absence and presence of p‐bromobenzyloxyamine (NSD‐1055), a DOPA‐decarboxylase inhibitor. In the absence of NSD‐1055, L‐DOPA produced a facilitation of impulse‐evoked release of noradrenaline at 0.1 μM but not at 1 and 10 μM, and had no effect on the spontaneous release. On the other hand, L‐DOPA 0.1 to 10 μM dose‐dependently increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…This facilitation seems to be due to L-DOPA itself but not due to the conversion from L-DOPA to DA, since qualitatively similar facilitatory actions of L-DOPA were seen even in the presence of an AADC inhibitor in rat striatal and hypothalamic slices (7,9,10). Thus a primary action of L-DOPA appears to be the facilitation of the evoked release of DA via presynaptic ,8-adrenoceptors even in striatal slices from this animal model for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This facilitation seems to be due to L-DOPA itself but not due to the conversion from L-DOPA to DA, since qualitatively similar facilitatory actions of L-DOPA were seen even in the presence of an AADC inhibitor in rat striatal and hypothalamic slices (7,9,10). Thus a primary action of L-DOPA appears to be the facilitation of the evoked release of DA via presynaptic ,8-adrenoceptors even in striatal slices from this animal model for Parkinson's disease.…”
Section: Discussionmentioning
confidence: 90%
“…In the course of studies on presynaptic regulatory mechanisms for the release of endogenous catecholamines from rat brain slices (12)(13)(14), we found that endogenous DOPA is released in response to depolarizing stimuli such as bipolar electrical field pulses, high K+ (8) and nicotine (11) from rat striatal slices in a transmitter-like manner. On the other hand, exogenously applied L-DOPA had, even under the inhibition of AADC, biphasic presynaptic regulatory actions on the release of noradrenaline and DA from rat hypothalamic and striatal slices via facilitatory Q-adrenoceptors and inhibitory DA-receptors (7,10). Especially, this facilitatory action of L-DOPA was seen at concentrations lower than those needed to produce the conversion to DA.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…However, this might not reflect the nature of OA1 in native cells because the possibility of a low expression of OA1 or other factors in such cell lines cannot be excluded. Indeed, nanomolar concentrations of DOPA can induce presynaptic regulation of impulse-evoked catecholamine release from brain slices (11,42). In in vivo experiments, DOPA at doses comparable to those of glutamate induces depressor and bradycardic response in the NTS of anesthetized rats (7,12).…”
Section: Dopa Che Behaves As An Antagonist Of Dopa In Oa1-expressing mentioning
confidence: 99%